2014
DOI: 10.1093/nar/gku1230
|View full text |Cite
|
Sign up to set email alerts
|

Abundance of the Fanconi anaemia core complex is regulated by the RuvBL1 and RuvBL2 AAA+ ATPases

Abstract: Fanconi anaemia (FA) is a genome instability disease caused by defects in the FA DNA repair pathway that senses and repairs damage caused by DNA interstrand crosslinks. At least 8 of the 16 genes found mutated in FA encode proteins that assemble into the FA core complex, a multisubunit monoubiquitin E3 ligase. Here, we show that the RuvBL1 and RuvBL2 AAA+ ATPases co-purify with FA core complex isolated under stringent but native conditions from a vertebrate cell line. Depletion of the RuvBL1-RuvBL2 complex in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
37
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(38 citation statements)
references
References 89 publications
1
37
0
Order By: Relevance
“…The delineation of sequences in ECD and RUVBL1 that mediate their interaction should help directly test whether selective abrogation of this interaction is functionally critical in cell cycle progression, as well as to assess the potential role of ECD in other roles of RUVBL1 within the R2TP complex. Interestingly, mouse ECD and RUVBL1 knockouts are phenotypically similar, since both are embryonic lethal at the blastocyst stage (6,19). RUVBL1 is essential for cellular proliferation as seen in knockout cells or upon knockdown of RUVBL1 expression (18).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The delineation of sequences in ECD and RUVBL1 that mediate their interaction should help directly test whether selective abrogation of this interaction is functionally critical in cell cycle progression, as well as to assess the potential role of ECD in other roles of RUVBL1 within the R2TP complex. Interestingly, mouse ECD and RUVBL1 knockouts are phenotypically similar, since both are embryonic lethal at the blastocyst stage (6,19). RUVBL1 is essential for cellular proliferation as seen in knockout cells or upon knockdown of RUVBL1 expression (18).…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have shown that, aside from the R2TP complex, RUVBL1/2 are also parts of other functionally relevant complexes, such as chromatin remodeling complexes TIP60, SWR/SRCAP, and INO80 and the Fanconi anemia core complex that controls DNA interstrand cross-link repair and function, and regulate telomerase biogenesis and mitosis (19,(43)(44)(45). Given the PIH1D1-independent interaction of ECD with RUVBL1, the potential roles of ECD via these alternative complexes will be of great future interest.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…RUVBL1 is essential for adult hematopoiesis in the mouse [5]. In U2OS cells (osteosarcoma cell line), depletion of RUVBL1 together with RUVBL2 leads to depletion of the Fanconi anemia core complex, which in turn leads to chromosomal instability [13]. Salzer et al [1] postulated that RUVBL1 may be part of a chaperone complex which could have a vital role in protecting mammalian RBCs under various stress conditions by associating with cytoskeletal or membrane components.…”
Section: Figmentioning
confidence: 99%
“…The helicases RUVBL1 and RUVBL2 (RUVBLs) exist in INO80, TIP60, and SRCAP yet their remodeling-related functions are largely unknown, due in part to the fact that the RUVBLs promiscuously participate in non-remodeling activities through the Fanconi Anemia complex [44] and in snoRNP assembly [45]. Assembly of INO80 and TIP60 has been shown to be dependent on the RUVBLs [46], [47].…”
Section: Accessory Subunits In Remodeler Activitiesmentioning
confidence: 99%